2016
DOI: 10.22302/iribb.jur.mp.v84i1.201
|View full text |Cite
|
Sign up to set email alerts
|

The Hevea brasiliensis AP2/ERF superfamily: from ethylene signalling to latex harvesting and physiological disease response

Abstract: Abstrak Etilen merupakan hormon yang dikenal karena perannya dalam proses penyadapan lateks di tanaman karet (Hevea brasiliensis)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
(66 reference statements)
1
2
0
Order By: Relevance
“…These DEGs and DAPs were significantly enriched in 28 KEGG pathways, which were mainly related to energy metabolism, carbohydrate metabolism, lipid metabolism, ROS scavenging, PCD, and signal transduction/information processing (Figure 2c ; Table S4 ). Thus, it can be concluded that TPD affects energy, carbohydrate, and lipid metabolism, as well as ROS scavenging, PCD, and signal transduction/information processing, which is consistent with the physiological parameters of latex from healthy and TPD‐affected trees and in agreement with previous studies (Chen et al., 2003 ; de Faÿ, 2011 ; Li et al., 2010 , 2016 ; Peng et al., 2011 ; Putranto & Montoro, 2016 ; Venkatachalam et al., 2009 ; Zhang et al., 2017 ). Notably, the correlation between DEGs and DAPs was very poor ( r = 0.024 in T2_H and r = 0.104 in T4_H), indicating that the protein abundance in the latex of TPD‐affected trees may be significantly affected by post‐translational modifications and splicing events (Pandey & Mann, 2000 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These DEGs and DAPs were significantly enriched in 28 KEGG pathways, which were mainly related to energy metabolism, carbohydrate metabolism, lipid metabolism, ROS scavenging, PCD, and signal transduction/information processing (Figure 2c ; Table S4 ). Thus, it can be concluded that TPD affects energy, carbohydrate, and lipid metabolism, as well as ROS scavenging, PCD, and signal transduction/information processing, which is consistent with the physiological parameters of latex from healthy and TPD‐affected trees and in agreement with previous studies (Chen et al., 2003 ; de Faÿ, 2011 ; Li et al., 2010 , 2016 ; Peng et al., 2011 ; Putranto & Montoro, 2016 ; Venkatachalam et al., 2009 ; Zhang et al., 2017 ). Notably, the correlation between DEGs and DAPs was very poor ( r = 0.024 in T2_H and r = 0.104 in T4_H), indicating that the protein abundance in the latex of TPD‐affected trees may be significantly affected by post‐translational modifications and splicing events (Pandey & Mann, 2000 ).…”
Section: Discussionsupporting
confidence: 91%
“…TPD seriously affects the NR yield and quality of rubber trees (Putranto & Montoro, 2016 ; Zhang et al., 2017 ). Previous studies investigated the molecular mechanisms of TPD using suppression subtractive hybridization and transcriptome sequencing analysis (Li et al., 2010 , 2016 ; Liu et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation